Re-trafficking of hERG reverses long QT syndrome 2 phenotype in human iPS-derived cardiomyocytes. (12th March 2014) - Mehta, Ashish; Sequiera, Glen Lester; Ramachandra, Chrishan J.A.; Sudibyo, Yuliansa; Chung, Yingying; Sheng, Jingwei; Wong, Keng Yean; Tan, Teng Hong; Wong, Philip; Liew, Reginald; Shim, Winston
Abstract: Aims: Long QT syndrome 2 (LQTS2) caused by missense mutations in hERG channel is clinically associated with abnormally prolonged ventricular repolarization and sudden cardiac deaths. Modelling monogenic arrhythmogenic diseases using human-induced pluripotent stem cells (hiPSCs) offers unprecedented mechanistic insights into disease pathogenesis. We utilized LQTS2-hiPSC-derived cardiomyocytes (CMs) to elucidate pathological changes and to demonstrate reversal of LQTS2 phenotype in a therapeutic intervention using a pharmacological agent, ( N -[ N -( N -acetyl-l -leucyl)-l -leucyl]-l -norleucine) (ALLN). Methods and results: We generated LQTS2-specific CMs (A561V missense mutation in KCNH2 ) from iPSCs using the virus-free reprogramming method. These CMs recapitulate dysfunction of hERG potassium channel with diminished I Kr currents, prolonged repolarization durations, and elevated arrhythmogenesis due to reduced membrane localization of glycosylated/mature hERG. Dysregulated expression of folding chaperones and processing proteasomes coupled with sequestered hERG in the endoplasmic reticulum confirmed trafficking-induced disease manifestation. Treatment with ALLN, not only increased membrane localization of mature hERG but also reduced repolarization, increased I Kr currents and reduced arrhythmogenic events. Diverged from biophysical interference of hERG channel, our results show that modulation of chaperone proteins could be therapeutic in LQTS2 treatment. Conclusion: Our in vitro study shows an alternative approach to rescue diseased LQTS2 phenotype via corrective re-trafficking therapy using a small chemical molecule, such as ALLN. This potentially novel approach may have ramifications in other clinically relevant trafficking disorders.